Seismic intensity investigation of the 2001 M=6.0 Yajiang-Kangding earthquake and discussion on its background of seismogenic structures - He, Yu-lin; Zhang, Qin; Huang, Wei (Acta seismologica sinica, 2002)
An M=6.0 earthquake occurred on February 23, 2001 in the western Sichuan Province, China. The macro seismic epicenter situated in the high mountain-narrow valley region between Yajiang and Kangding counties. According to field investigation in the region, the intensity of epicentral area reached VIII and the areas with intensity VIII, VII and VI are 180 km2, 1 472 km2 and 3 998 km2, respectively. The isoseismals are generally in elliptic shape with major axis trending near N-S direction. The earthquake destroyed many buildings and produced some phenomena of ground failure and mountainous disasters in the area with intensity VIII. This event may be resulted from long-term activities of the Litang fault and Yunongxi fault, two main faults in the western Sichuan. The movements between the main faults made the crust stress adjusted and concentrated, and finally the earthquake on a secondary fault in the block released a quite large energy.